Evaluation of Morphological Changes in Breast Cancer: Influence of Fractal Meta-Analysis: - Mirmalek, SeyedAbbas; Yarandi, Niloofar sadat; Tafazoli Shadpour, Mohammad; Saatian, Minoo; Raeesi, Homa; Jafargholi Rangraz, Esmaieel; Salehi, Masoud; Salimi Tabatabaee, Seyed Alireza (Galen Medical Journal, 2014)
Many studies suggested that fractals could be brought in any structural anarchy, such as cancers, for diagnosis and prognosis evaluation by quantifying it and expressing it in terms of fractal geometry. In this study, we aimed to evaluate pathologic grades or breast carcinomas by fractal analysis. This cross-sectional study was performed on 60 women with breast ductal carcinoma. From all the patients some photographs from the smears with pathological standard and with a digital camera were taken to analyze them by MATLAB software via Box-Counting method. The used analytical methods were ANOVA and T tests. There was a significant association between fractal count and the pathological grade (P<0.05). According to the findings of this study, fractal count was a prognostic indicator in breast cancer patients. However, we recommended performing further studies with higher sample size and in other types of cancers.